2017
DOI: 10.3141/2616-02
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Geometric Factors on Lateral Position of Vehicles in Freeway Buffer-Separated Managed Lanes

Abstract: Chapter 3 in the 2004 AASHTO high-occupancy-vehicle guidelines includes a prioritized trade-off table of various design options for high-occupancy-vehicle lanes (now known as managed lanes). The design trade-offs include the reduction of lane, shoulder, or buffer width. The key measure thought to be affected by lane, shoulder, and buffer width is lateral position. The presented study identified the relationship between operations and cross-section width, including the type of buffer design separating the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The DAA does not damage the muscles around the hip joint, does not cause significant damage to the posterior structures of the hip capsule, and has a better postoperative balance of lower limb muscle strength than the traditional approach, so it has the accuracy of prosthesis placement and good postoperative hip stability, reducing the risk of postoperative soft tissue imbalance caused by periprosthetic muscle injury and postoperative hip dislocation caused by improper placement of the prosthesis [ 22 ]. Daily activities such as squatting, sitting on a low stool, and bending to put on socks and laces can be performed in the early postoperative period, and no special protection is needed for the postoperative hip joint [ 23 25 ]. In this paper, we used imaging to observe the angle of the posterior prosthesis and showed that hip arthroplasty using the direct anterior approach improved hip mobility in early stages compared with other approaches and reduced pain.…”
Section: Introductionmentioning
confidence: 99%
“…The DAA does not damage the muscles around the hip joint, does not cause significant damage to the posterior structures of the hip capsule, and has a better postoperative balance of lower limb muscle strength than the traditional approach, so it has the accuracy of prosthesis placement and good postoperative hip stability, reducing the risk of postoperative soft tissue imbalance caused by periprosthetic muscle injury and postoperative hip dislocation caused by improper placement of the prosthesis [ 22 ]. Daily activities such as squatting, sitting on a low stool, and bending to put on socks and laces can be performed in the early postoperative period, and no special protection is needed for the postoperative hip joint [ 23 25 ]. In this paper, we used imaging to observe the angle of the posterior prosthesis and showed that hip arthroplasty using the direct anterior approach improved hip mobility in early stages compared with other approaches and reduced pain.…”
Section: Introductionmentioning
confidence: 99%
“…Among road geometric factors, influences of lane width and shoulder width on LP of vehicles were examined. It was thoroughly reported in literature (Lindheimer et al 2017;Mecheri et al 2017) that vehicles are shifting away from the edge of carriageway as lane width increases. On the other hand, with the increase in shoulder width, vehicles shift laterally towards the edge of carriageway (Van Driel et al 2004;Mecheri et al 2017;Lindheimer et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It was thoroughly reported in literature (Lindheimer et al 2017;Mecheri et al 2017) that vehicles are shifting away from the edge of carriageway as lane width increases. On the other hand, with the increase in shoulder width, vehicles shift laterally towards the edge of carriageway (Van Driel et al 2004;Mecheri et al 2017;Lindheimer et al 2017). Also, treatments like installation of rumble strips, have impacts on lateral placement of vehicles (Porter et al 2004;Gates et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations